The Influence of Social Media Interactivity, User Experience and Brand Image on Customer Engagement in Digital Platforms of Digital-Based Retail Customers - Indri Yani; Andi Herlina; Darwis Darwis; Vivid Violin; Haniwijaya Pahlawansah; Fransisca Dyah Anggraini (Journal of Information System, Technology and Engineering, 2026)
The objective of this study is to examine the influence of Social Media Interactivity, User Experience, and Brand Image on Customer Engagement on Digital Platforms for digital-based retail consumers. Data were collected via online surveys and analyzed by using multiple linear regression. Before testing the hypotheses, validity and reliability tests, as well as the conventional assumption tests. The research results pointed out that Social Media Interactivity, User Experience, and Brand Image have a significant and positive impact on Customer Engagement in Digital Platforms partly and simultaneously. The leading variable impacting Customer Engagement is User Experience. The results of the study indicate that the quality of social media engagement, the best user experience, and a strong brand image may contribute to an increase in consumer contact on digital platforms. This research advances the literature of digital marketing, customer engagement, and consumer behavior, and offers practical implications for digital-based retail organizations to develop strategies to sustainably enhance customer engagement.